In vitro Propagation of Bitter Gourd (Momordica charantia L.) from Nodal and Root Segments - Munsur, M.A.Z. Al; Haque, M.S.; Nasiruddin, K.M.; Hossain, M.S. (Plant Tissue Culture and Biotechnology, 2010)
Explants of nodal and root segments of bitter gourd were cultured on MS supplemented with various concentrations of BAP in combination with either 2,4-D or NAA. Nodal segments produced the highest percentage (93.75) of callus in MS supplemented with 1.0 mg/l 2,4-D and 1.0 mg/l BAP whereas, root segments produced the highest (85.00%) callus in 0.6 mg/l NAA and 2.5 mg/l BAP combination. A combination of 1.0 mg/l 2,4-D and 1.0 mg/l BAP exhibited 75.00% shoot regeneration from nodal segments. The highest shoot length (5.15 cm) was recorded with 2.5 mg/l BAP and 0.2 mg/l IAA from nodal segments. No sign of regeneration of shoot was found from root segments in any of the combinations. However, some combinations produced only roots. Key words: In vitro propagation, bitter gourd, nodal segments, Root segments D.O.I. 10.3329/ptcb.v19i1.4916 Plant Tissue Cult. & Biotech. 19(1): 45-52, 2009 (June)